2022
DOI: 10.3389/fpsyt.2022.896938
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between living arrangements and depression among older adults in Shandong, China: The mediating role of social support

Abstract: BackgroundLiving arrangements and social support have an impact on depression among older adults. However, the underlying mechanism between those variables remains unknown. This study aims to investigate the mediating role of social support in the relationship between living arrangements and depression among older adults.Materials and methodsMulti-stage stratified sampling method was used to select 3,859 older adults from Taian City, Shandong Province, China, for cross-sectional investigation. Living arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…All evidence suggests that living with family members is a protective factor for the occurrence of depression in older adults.In addition, our study found that older people living in nursing homes have a higher risk of depression compared to those living alone. Previous scholarship suggests that living with others is more likely to result in better social support than living alone, thus reducing the risk of depression in older adults [4]. The reasons for this contradictory result remain unclear and need to be explored in further studies.We also found no correlation between LA and anxiety in older adults, with some studies reporting signi cant differences in anxiety, depression in LA, and a nonsigni cant effect of LA on anxiety in the nal model corrected for covariates [40].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…All evidence suggests that living with family members is a protective factor for the occurrence of depression in older adults.In addition, our study found that older people living in nursing homes have a higher risk of depression compared to those living alone. Previous scholarship suggests that living with others is more likely to result in better social support than living alone, thus reducing the risk of depression in older adults [4]. The reasons for this contradictory result remain unclear and need to be explored in further studies.We also found no correlation between LA and anxiety in older adults, with some studies reporting signi cant differences in anxiety, depression in LA, and a nonsigni cant effect of LA on anxiety in the nal model corrected for covariates [40].…”
Section: Discussionmentioning
confidence: 94%
“…As one of the countries with the most serious aging population, China is characterized by large number, fast speed, large differences and heavy tasks [2].In 2021, the country's order population aged 60 and above is excepted to reach 264 million, accounting for 18.7% of the total population [3]. Compared with 2010, the proportion of the older population aged 60 and above in the total population in China increases by 5.44 percentage points in 2020 [4,5]. How to better promote healthy aging is an important issue that needs to be urgently addressed worldwide at present.…”
Section: Introductionmentioning
confidence: 99%
“…Along with previous studies, the current study also indicates that there is an increasing trend of depressive symptoms among the elderly with increasing age, irrespective of gender (29)(30)(31). The relationship between living arrangements-such as living alone, with a spouse, or with children-and depressive symptoms (32,33). Elderly individuals who reside with their spouses and children exhibit a lower likelihood of experiencing depression compared to those living alone (34).…”
Section: Decomposition Of the Migrant-non-migrant Gap In Depressionmentioning
confidence: 99%
“…on depression must be confirmed by further research. Second, living arrangements may have influenced depression among the older population [42]. Unlike older people in developed countries who spend their later lives living with no adult children or in long-term care facilities [43], the majority of Vietnamese older adults are cared for by their offspring in houses where many generations live together [44].…”
Section: Plos Onementioning
confidence: 99%